Eesti ajalugu kui müüt: vaatenurga probleem - Kalmo, Hent (Acta historica Tallinnensia, 2022)
National history is often opposed to transnational history and considered an outdated approach to studying the past. Yet it is unclear why this should be so, especially if national history is defined merely by a concern with what is perceived as national and not wedded to any particular methodology. The article sets out to analyse the various meanings of national history by exploring one of its manifestations in action: the ‘Estonian orientation’ that arose in the 19th century and came into conflict with existing Baltic German historiography. The ‘Estonian paradigm’, as Jaan Undusk has characterised it, is interesting not only as an example of national history (of which there are, of course, many) but also because of the way its exponents described their own intervention. They claimed to ‘write history from the point of view of Estonians’. It can thus be seen as a predecessor of later attempts to change the viewpoint from which history is written (for example ‘history from below’, animal or environmental history). In order to examine more closely the role of viewpoint in history writing, the article begins by setting out the differences between the Estonian and Baltic German orientations as they had developed by the 1930s. The Estonian historian Hans Kruus deserved particular attention since he was the first to offer a theoretical account of the effects of an historian’s social position upon the work produced. Whilst his analysis was a rather crude application of Marxism, it led him to distinguish between various forms of bias: a tendency to privilege certain subject matter and a tendency to treat it in a manner most favourable to one’s social group. The emergence of a rival body of work, strongly revisionist in character, also prompted a few Baltic Germans (for example Arved von Taube) to appreciate the importance of viewpoint in history writing. After following this parallel development (it can hardly be seen as an exchange, since Estonians and Baltic Germans never engaged with each other on such theoretical matters), the article moves on to ask if the two orientations were really as dissimilar as they were made out to be. I suggest that the two, although starkly contrasted in their depiction of historical events, were representative of a shared tradition of homeland history (Vaterlandsgeschichte).